The potential for justice through tourism - Freya Higgins-Desbiolles (Via@)
This article considers the potential for tourism to contribute to efforts to secure justice. It reviews the evolution of tourism from a respected tool for personal development and social transformation to its now industrialised form under neoliberalism where its value is estimated in terms of employment and income. Despite this context, recognition that the justice issues of tourism and justice capacities of tourism are worthy of analysis has grown in the 2000s. Justice tourism takes many forms and is facilitated by a number of means and stakeholders, but at its core it is focused on ensuring tourism delivers more sociologically and ecologically benign forms of tourism development which create better futures for all stakeholders, but particularly the hosting communities. Efforts to make tourism more responsible, ethical and just have been critiqued, both from a neoliberal perspective that tourism is not a site for moralisation and from a critical race positioning that many forms of justice tourism might not attain their goals of solidarity and emancipation.Looking forward, this analysis suggests that it is imperative that future research and action addresses the larger structural issues of justice and that the critical tourism studies movement is potentially a promising vehicle for this work. Additionally challenging contemporary times demand renewed and more rigorous focus. Future topics to consider include structural issues of mobility in a precarious world, climate injustices, justice for non-human others in the era of the Anthropocene and diverse paradigms and worldviews for thinking through justice tourism.